Strabismus Surgery and its Complications - Coats, David K.; Olitsky, Scott E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Strabismus Surgery and its Complications is divided into two is provided based on evidence-based medicine where available. distinct sections. Part I outlines the surgical management of Consensus and/or common sense advice is provided where - strabismus in 17 chapters. A full range of topics is covered idence-based medicine is not available. A chapter on managing including basic anatomy and physiology, surgical planning, patients with atypical and unexpected anatomical features and preoperative and postoperative management, and surgical a chapter on the medicolegal aspects of strabismus surgery are techniques. Surgical techniques are described in dedicated included. Te textbook is extensively referenced and indexed chapters, each richly illustrated with fgures and photographs. to facilitate rapid identifcation and review of desired inform -a Detailed descriptions of the basic steps of surgery as well as tion. Cross-reference is made throughout each chapter to other surgical nuances are provided. Te fgures and fgure legends chapters containing related information. are designed to stand alone as basic surgical instruction for the A DVD is provided containing video footage of basic su- surgeon who has experience with the surgical management of gical techniques to compliment the information on surgical strabismus. More detailed instruction is available in the text for techniques provided in Part I of the textbook. Te DVD also those wanting elaboration.
Surgical Management of Strabismus -- Surgically Important Anatomy -- Physiology of Eye Movements -- Indications for Strabismus Surgery -- Surgical Decision Making -- Preoperative and Postoperative Care -- Anesthesia Considerations -- Equipment, Operating Room Supplies, and Patient Preparation -- Techniques of Exposure and Closure and Preliminary Steps of Surgery -- Recession of the Rectus Muscles and Other Weakening Procedures -- Resection of the Rectus Muscles and other “Strengthening” Procedures -- Surgery on the Inferior Oblique Muscle -- Surgery on the Superior Oblique Tendon -- Transposition Procedures -- Adjustable Suture Techniques -- Special Procedures -- The Use of Botulinum Neurotoxin in the Treatment of Strabismus -- Nonsurgical Treatment of Strabismus -- Complications of Strabismus Surgery -- Preoperative Management Errors -- Anterior Segment and Ocular Surface Complications of Strabismus Surgery -- Anterior Segment Ischemia -- Scleral Perforation and Penetration -- Postoperative Infection -- Slipped and Lost Muscles -- Hemorrhage -- Adherence and Adhesion Syndromes -- Complications Involving the Ocular Adnexa -- Unexpected and Atypical Anatomy -- Anesthesia-Related Complications -- Unexpected Postoperative Alignment -- Altered Postoperative Vision -- Persistent Diplopia Following Surgery -- Medicolegal Aspects of Strabismus Surgery.
Keywords: Ophthalmology; Ophthalmology